2022
DOI: 10.1108/hff-11-2021-0730
|View full text |Cite
|
Sign up to set email alerts
|

MHD flow of a nanofluid due to a nonlinear stretching/shrinking sheet with a convective boundary condition: Tiwari–Das nanofluid model

Abstract: Purpose Nanofluid research has piqued the interest of scientists due to its intriguing applications in nanoscience, biomedical and electrical engineering, medication delivery, biotechnology, food processing, chemotherapy and other fields. This paper aims to inspect the behavior of the mixed convection magnetohydrodynamic flow and heat transfer induced by a nonlinear stretching/shrinking sheet in a nanofluid with a convective boundary condition. Tiwari and Das mathematical nanofluid model is incorporated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Some of the important contributions of nanofluids are in many studies. [22][23][24] Hybrid nanoliquids have higher thermal conductivity than nanoliquids as well as basic liquids. In comparison with base fluid containing single-type nanoparticles, hybrid nanoliquids have comparable applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the important contributions of nanofluids are in many studies. [22][23][24] Hybrid nanoliquids have higher thermal conductivity than nanoliquids as well as basic liquids. In comparison with base fluid containing single-type nanoparticles, hybrid nanoliquids have comparable applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofluids are widely utilized in space engineering technology, microwaves, production of generic medicines, biosensors, equipment used for cooling, furnace gas outlets, caloric regulating, nuclear reactors, medicinal approaches, combustion cells, and a variety of other scientific and technical sectors. Some of the important contributions of nanofluids are in many studies 22–24 . Hybrid nanoliquids have higher thermal conductivity than nanoliquids as well as basic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The work shows that improvement in the average Nusselt number can reach 65% for some combinations of the influencing physical parameters. The Tiwari–Das nanofluid model has been used in Khan et al (2022) to determine heat transfer induced by a stretching sheet in a nanofluid. Several other works are carried out with this technique combining porous media and nanofluids, including Martin et al (2021), Sheikholeslami (2017b) and Baïri (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The stagnation point flow of a conductive nano-liquid across a stretching surface under the influence of radiation and dissipation effects was illustrated by Kiran Kumar et al 33 Few studies on nanofluids are found in the work by authors. 3438…”
Section: Introductionmentioning
confidence: 99%
“…The stagnation point flow of a conductive nano-liquid across a stretching surface under the influence of radiation and dissipation effects was illustrated by Kiran Kumar et al 33 Few studies on nanofluids are found in the work by authors. [34][35][36][37][38] In recent years, many researchers have concentrated on hybrid nanofluids. Hybrid nanofluid is a mixture of two different forms of nanoparticles added in the base fluids.…”
Section: Introductionmentioning
confidence: 99%